In vivo modelling of cutaneous T-cell lymphoma: The role of SOCS1 - Luo, Yixin; Vermeer, Maarten H.; de Gruijl, Frank R.; Zoutman, Willem H.; Sluijter, Marjolein; van Hall, Thorbald; Tensen, Cornelis P. (Frontiers in Oncology, 2022)
Mycosis fungoides (MF), the most common type of Cutaneous T cell Lymphoma (CTCL), is characterized by an inflamed skin intermixed with proliferating malignant mature skin-homing CD4+ T cells. Detailed genomic analyses of MF skin biopsies revealed several candidate genes possibly involved in genesis of these tumors and/or potential targets for therapy. These studies showed, in addition to common loss of cell cycle regulator CDKN2A, activation of several oncogenic pathways, most prominently and consistently involving JAK/STAT signaling. SOCS1, an endogenous inhibitor of the JAK/STAT signaling pathway, was identified as a recurrently deleted gene in MF, already occurring in the earliest stages of the disease. To explore the mechanisms of MF, we create in vivo mouse models of autochthonous CTCLs and these genetically engineered mouse models (GEMMS) can also serve as valid experimental models for targeted therapy. We describe the impact of allelic deletion of Socs1 in CD4 T cells of the skin. To achieve this, we crossed inducible Cre-transgenic mice in the CD4 lineage with transgenic mice carrying floxed genes of Socs1. We first determined optimal conditions for Socs1 ablation with limited effects on circulating CD4 T-cells in blood. Next, we started time-course experiments mimicking sustained inflammation, typical in CTCL. FACS analysis of the blood was done every week. Skin biopsies were analyzed by immunocytochemical staining at the end of the experiment. We found that the Socs1 knockout transgenic group had thicker treated skin compared with the control group and had more CD3 and CD4 in the skin of the transgenic group compared to the control group. We also noted more activation of Stat3 by staining for P-Stat3 in Socs1 knockout compared to wt CD4+T cells in the skin. The results also indicated that single copy loss of Socs1 in combination with sustained inflammation is insufficient to start a phenotype resembling early stage mycosis fungoides within eight weeks in these mice. In sum, we developed and optimized an autochthonous murine model permitting selective knockout of Socs1 in skin infiltrating CD4 T-cells. This paves the way for more elaborate experiments to gain insight in the oncogenesis of CTCL